2003
DOI: 10.1046/j.0902-4441.2003.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin‐15 on anti‐CD3/anti‐CD28 induced apoptosis of umbilical cord blood CD4+ T cells

Abstract: IL-15 preferentially resulted in an activation-enhancing effect on CB CD4+ T cells, accompanied by increased apoptosis. Our finding may have therapeutic implications while designing IL-15 immunotherapy for patients receiving CB transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
(31 reference statements)
0
11
1
Order By: Relevance
“…CD3/TCR signaling activates STAT5 and when this signaling leads to apoptosis, it is dependant on Fas/FasL interactions [48,49]. IL-15 exacerbates apoptosis in CD4+ T cells activated with anti-CD3 and anti-CD28, potentially by recruiting more blasts capable to die [50]. AgICD requires Fas/FasL interactions, does not require perforin or granzymes, and TNF-α is thought to play a late role in the process [51].…”
Section: Discussionmentioning
confidence: 99%
“…CD3/TCR signaling activates STAT5 and when this signaling leads to apoptosis, it is dependant on Fas/FasL interactions [48,49]. IL-15 exacerbates apoptosis in CD4+ T cells activated with anti-CD3 and anti-CD28, potentially by recruiting more blasts capable to die [50]. AgICD requires Fas/FasL interactions, does not require perforin or granzymes, and TNF-α is thought to play a late role in the process [51].…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that survival of CB T cells post-activation can be improved to a greater degree by IL-15 than their adult counterparts. The timing of IL-15 administration is important, as IL-15 promotes AICD of CB CD4 + T cells when used with TCR cross-linking [18] while serving as a survival factor when PHA-activated CB MNCs were washed before culture with IL-15.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous reports have addressed the deficient CB T and NK function compared to adults and their enhancement with IL-15 [18,27], suggesting that IL-15 immunotherapy may alleviate the problems of delayed engraftment and infection susceptibility following CB transplantation. In addition to its IL-2-like activities, we demonstrated in the present study the unique effect of IL-15 on the survival enhancement and apoptosis protection of PHA activated CB T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While UCB-derived T cells can be propagated ex vivo, [43][44][45][46][47][48][49] the functional immaturity of T cells in circulating umbilical cord blood typically prevents ex vivo identification of endogenous leukemia/ lymphoma-specific T cells. Therefore, we developed a genetic engineering strategy to introduce a chimeric immunoreceptor in order to generate UCB-derived T cells with desired specificity.…”
Section: Discussionmentioning
confidence: 99%